The Spatial Distribution Analysis Of The Human Development Index (HDI) In Depok City, West Java - Murshalin Nissa Ratu; vidyana; Meliyani Siti (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2026)
Human Development is a concept that encompasses efforts to enhance human well-being and potential. Depok City, as an integral part of urban development in Indonesia, experiences population growth, urbanization, and social changes that significantly impact the quality of life of its residents. Therefore, this research is crucial. The purpose of this study is to determine the Human Development Index (HDI) in Depok City and identify the distribution of the HDI in Depok City for the years 2018, 2020, and 2022. The method used involves a quantitative approach based on the 2016 Central Statistics Agency guidelines and utilizes Geographic Information Systems (GIS) to analyze spatial distribution data. The research results indicate that Depok City's HDI shows a positive trend, with an increase each year. Depok City's HDI is divided into two classes: high, which is spread in the western and eastern parts, and very high, which is spread in the northern part and extends to the southern part of Depok City.